Strategic Planning Of Enterprise’s Activity On A Basis Of Application Of The Balanced Scorecard - Бегун, Світлана Іванівна; Бортнік, Світлана Миколаївна; Begun, Svitlana I.; Bortnik, Svitlana M. (Wydawnictwo Kujawsko-Pomorskiej Szkoły Wyższej w Bydgoszczy, 2016)
The article is dedicated the improvement of methods of the strategic planning of enterprises activity for providing its greater effectiveness and practicality in application. This days the Ukrainian enterprises have problem of absence of the management strategic instruments adapted to the market conditions. Namely – a base index after which it is possible to measure progress of the strategy realization and functioning efficiency of firm is absent. A research purpose is a scientific ground of application of the strategic planning tools on production enterprises in the conditions of unstable external environment. The purpose of the article is forming of the indicators evaluation system which would allow quickly and effectively trace changes in external and internal surroundings of enterprise and to react on them quickly. Task to the article is forming of the balanced scorecard system and complex estimation of using of the enterprise strategic potential resource; calculation of the enterprise strategic development scorecards; development of the enterprise strategic contour. Research results are: directions of improvement of development of the enterprise balanced scorecard system by the calculation of integral indexes of success in the key spheres of the enterprise functioning. Methodology of construction of strategic contour of the enterprise activity is proposed.
Keywords: Balanced Scorecar system; strategy; strategic planning; strategic aims; indicator of strategic development of enterprise; strategic contour